Personalised education in current pedagogical renewal centers - Carmen Romero García; Francisco Javier Pericacho Gómez; Olga Buzón García; Jordi Feu Gelis (OmniaScience, 2024)
Pedagogical renewal is a concept loaded with a historical-pedagogical trajectory linked to reflection, social justice, educational improvement, teacher commitment and the questioning of the educational model, with personalised education being a key aspect. The aim of this paper is to analyse how learning is personalised in primary education centres that promote processes of pedagogical renewal. A qualitative methodology is used, based on a case study. Two schools with a high intensity of pedagogical renewal were selected and in-depth interviews were conducted with the management team and teachers, focus groups with families and students, and participant observation. The information derived is analysed with the ATLAS.Ti 22 programme, after coding and categorisation. The results reveal a number of common elements and processes of personalisation of learning which are structured in three dimensions. In the first dimension, school characteristics, the following stand out: student autonomy, individualisation of learning and freedom of choice of learning pathways. As for the second dimension, educational project, the following elements stand out: flexible curricular organisation, active methodology where group work is a key element, organisation of timetables without previously established patterns, the role of accompanying teachers, student focus and active participation of families in daily school life. Finally, from the third dimension, inclusion, the following can be extracted: daily educational work where diversity is not a limitation, but a source of learning of great didactic value.